Bruns–Garland syndrome precipitated by anti-tuberculous therapy in a patient with type 2 diabetes mellitus - Sasikumar, Amithkumar; S, Sheetal (Nepal Journal of Neuroscience, 2022)
India has a high prevalence of tuberculosis as well as diabetes mellitus, and both contribute to a major disease burden. Diabetes mellitus increases the risk of tuberculosis. Patients with diabetes are more prone to develop cavitary lesions than non-diabetics. Tuberculosis can worsen the glycemic status of an individual and anti-tuberculous drugs like Rifampicin can interact with oral anti-diabetic drugs, further worsening the glycemic control. This can result in complications related to diabetes, like diabetic amyotrophy. We hereby report the case of a 69-year-old gentleman with diabetes mellitus, who developed uncontrolled blood sugars, leading to Bruns Garland syndrome or diabetic amyotrophy on starting anti-tuberculous therapy for sputum positive pulmonary tuberculosis.